2018
DOI: 10.1101/445817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Processing of grassland soil C-N compounds into soluble and volatile molecules is depth stratified and mediated by genomically novel bacteria and archaea

Abstract: Soil microbial activity drives the carbon and nitrogen cycles and is an important determinant of atmospheric trace gas turnover, yet most soils are dominated by organisms with unknown metabolic capacities. Even Acidobacteria, among the most abundant bacteria in soil, remain poorly characterized, and functions across groups such as Verrucomicrobia, Gemmatimonadetes, Chloroflexi, Rokubacteria are understudied. Here, we resolved sixty metagenomic, and twenty proteomic datasets from a grassland soil ecosystem and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Using these guilds, we determined the prevalence of three d-CAZy transcriptional strategies in the rhizosphere, and found that rhizosphere organisms upregulate decomposition transcripts in addition to increasing population sizes. Further, these populations used both primary and breakdown products, and supports recent observations that metabolic handoffs link together interacting members of microbial communities (79)(80)(81). Guilds dynamics of carbohydrate depolymerization during rhizosphere succession provides a key step towards developing microbially-constrained models to predict the fate of soil carbon.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Using these guilds, we determined the prevalence of three d-CAZy transcriptional strategies in the rhizosphere, and found that rhizosphere organisms upregulate decomposition transcripts in addition to increasing population sizes. Further, these populations used both primary and breakdown products, and supports recent observations that metabolic handoffs link together interacting members of microbial communities (79)(80)(81). Guilds dynamics of carbohydrate depolymerization during rhizosphere succession provides a key step towards developing microbially-constrained models to predict the fate of soil carbon.…”
Section: Discussionsupporting
confidence: 72%
“…Genome-resolved metagenomic analyses indicate the importance of metabolic byproduct handoff in linking together interacting members of microbial communities (80,81). The breadth of carbohydrate degradation pathways that Rhizosphere and Detritusphere guilds engage in may be a potential explanation for the stable, positive and repeatable interaction networks in the rhizosphere that we observed in a previous study (82).…”
Section: Metatranscriptomic Guilds Provide a Framework To Understand mentioning
confidence: 67%
See 1 more Smart Citation
“…These groups are widely distributed in ne earth, most of them showing a positive correlation with pH and a negative relationship with nutrient elements, such as soil organic carbon, TN, and available phosphorus [35,36]. The genomes of Acidobacteria encode large enzyme complements for degrading complex carbohydrates, which, in turn, impacts on the carbon distribution in the soil [37]. The bacteria from Chloro exi and WPS-2 were strongly associated with physicochemical soil properties, such as pH, AS, and TN, and Chloro exi were able to scavenge organic matter like sucrose, glucose, and N-acetyl-glucosamine under anoxic conditions [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The genomes of bacteria from the Verrucomicrobia and Rokubacteria contain some of the earliest dissimilatory sul te reductases to induce sul te/sulfate reduction, and thus play an important role in the global sulfur cycle [44]. The genome of Rokubacteria also exhibits an extensive capacity to biosynthesize diverse small organic molecules that promote mineral dissolution [37]. This may explain why stony soils were richer in nutrients than non-stony soils in both the BS and RZS samples ( Table 2).…”
Section: Discussionmentioning
confidence: 99%